Analisis strategi bank syariah indonesia dalam mengelola risiko pembiayaan mudharabah dan musyarakah pada sektor umkm - Syamil, Muhammad (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the strategies of Bank Syariah Indonesia (BSI) in managing risk in Mudharabah and Musyarakah financing to MSMEs. The research employs a mixed-methods approach, using quantitative data such as financial ratios (NPF, FDR, financing growth) of BSI during 2019–2024, and qualitative data from BSI’s risk management policy documents. Analysis is carried out using a combination of risk analysis and SWOT analysis, operationalized by expert panel scoring. The results indicate that the primary risks in Mudharabah and Musyarakah financing include loan defaults, moral hazard, and market uncertainties in MSME sectors. The most effective mitigation strategies include portfolio diversification, enhanced character screening, regular monitoring, MSME education and assistance, and implementation of monitoring technology. Practical implications of this research are internal policy recommendations for BSI to strengthen post-disbursement monitoring and evaluation systems, and expand collaboration with government institutions and MSME support agencies.